Implementing Adaptive Techniques in Systems for Collaborative Learning by Extending IMS-LD Capabilities - Magnisalis, Ioannis D; Demetriadis, Stavros N; Pomportsis, Andreas S (2010 2nd International Conference on Intelligent Networking and Collaborative Systems, 2010)
In this article we present an architecture for the integration of external and independent software components into IMS-LD based courses that cater for adaptivity. The architecture allows combining existing research on explicit representations of collaborative learning processes (i.e. learning designs) with the availability of existing and tested collaborative learning tools (e.g. a forum in a VLE, an agent, a service or even a software component that provides a specific functionality). The architecture allows controlling the learning tools either by a human or a pedagogical agent and thus enables adaptive interventions to the flow of the learning activity. A mediator component is the key element in the proposed architecture. To prove the soundness of the architecture and the flexibility of its implementation an example scenario is illustrated. In this scenario IMS-LD based modeling and Copper core engine are used to implement adaptations by setting LD properties according to input from an external group formation tool. The whole process is mediated by an integration component provided to the teacher as a Moodle resource.